Increasing understanding of biology concepts through writing scientific papers during the pandemic - Anisa Anisa; Rhiza Fitri Salsabila (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Learning activities were carried out online during the Covid-19 pandemic. Students must improve their ability to write biological scientific papers and apply them in the real world, even presenting them during distance learning. This research is classroom action research that aims to improve the mastery of cell transport concepts and their ability to write scientific papers through online learning. The research was conducted in class XI MIPA 1 at SMA Negeri 2 Purwakarta with 36 students with three cycles of treatment using a constructivist approach with a modified inquiry model. Each cycle is based on a reflection of the previous cycle. The test result data in each cycle is analyzed by comparing the data before and after treatment. Observation data about scientific writing components was analyzed to identify difficulties experienced by students. The results showed that the average learning outcomes for mastery concepts increased by 54.2% using the N-gain score, which means that the treatment significantly impacts mastering the concept of cell transport. The ability of scientific writing papers shows an increase of 11.25%. These classroom action research results show that making scientific writing papers can improve mastery of cell transport, and this may be a recommendation for teaching methods on other concepts.Abstrak Kegiatan pembelajaran dilaksanakan secara daring selama pandemi covid 19. Kemampuan peserta didik dalam menulis karya ilmiah biologi dan menerapkannya dalam dunia nyata penting ditingkatkan, bahkan presentasi saat belajar jarak jauh. Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan penguasaan konsep transportasi sel, dan meningkatkan kemampuan menulis karya ilmiah dengan pembelajaran daring. Penelitian ini dilaksanakan di kelas XI MIPA 1 SMA Negeri 2 Purwakarta yang berjumlah 36 siswa, dengan perlakuan 3 siklus menggunakan pendekatan konstruktivisme dengan model inkuiri yang dimodifikasi. Setiap siklus didasarkan pada refleksi dari siklus sebelumnya. Data hasil tes setiap siklus dianalisis dengan membandingkan data sebelum dan sesudah perlakuan. Data observasi tentang komponen penulisan ilmiah dianalisis untuk mengidentifikasi kesulitan yang dialami siswa. Hasil penelitian menunjukkan bahwa rata-rata hasil belajar penguasaan konsep meningkat sebesar 54,2% dengan menggunakan skor N-gain yang berarti perlakuan berpengaruh signifikan terhadap penguasaan konsep transportasi sel. Kemampuan menulis karya ilmiah menunjukkan peningkatan sebesar 11,25%. Hasil penelitian tindakan kelas ini menunjukkan bahwa pembuatan karya tulis ilmiah dapat meningkatkan penguasaan konsep transportasi sel, dan dapat menjadi rekomendasi metode pengajaran pada konsep lainnya.